CLINICAL AND DIAGNOSTIC SIGNIFICANCE OF ENDOMETRIAL IMPLANTATION MARKERS IN WOMEN WITH INFERTILITY - Jalolova , G.S.; Shukurov, F.I.; Jurayeva , A.J. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Introduction: The success of embryo implantation largely depends on endometrial receptivity, which is regulated by specific molecular biomarkers. Early detection of these markers is essential for diagnosing and predicting causes of infertility. Objective: To assess the expression and clinical–diagnostic significance of the endometrial implantation biomarkers — BCL6, CXCL13, and ZBTB16 — in infertile women. Materials and Methods: A total of 80 reproductive-aged women were included (mean age 32.0±4.8). The main group (n=50) consisted of patients with idiopathic infertility and endometrial dysfunction; the control group (n=30) included women with confirmed natural pregnancies. Biomarker levels were assessed via immunohistochemistry in luteal-phase endometrial biopsies. Results: BCL6 and CXCL13 were significantly overexpressed, and ZBTB16 underexpressed in the main group compared to controls (p<0.01). Strong inverse correlations were observed between BCL6 and implantation success (r=–0.71), and moderate for CXCL13 (r=–0.59); ZBTB16 showed a moderate positive correlation (r=+0.64). ROC analysis identified optimal cut-off values: BCL6 — 1.4 score (Se 80%, Sp 78%), ZBTB16 — 0.75 score (Se 76%, Sp 80%). Conclusion: The expression profiles of BCL6, CXCL13, and ZBTB16 provide clinically valuable diagnostic and prognostic information, supporting their use in personalized reproductive strategies and in improving implantation outcomes in infertile women.